Prevalence of sarcopenia after remission of hypercortisolism and its impact on HRQoL. (6th August 2021) - Martel‐Duguech, Luciana; Alonso‐Jimenez, Alicia; Bascuñana, Helena; Díaz‐Manera, Jordi; Llauger, Jaume; Nuñez‐Peralta, Claudia; Montesinos, Paula; Webb, Susan M.; Valassi, Elena
Abstract: Background: Cushing's syndrome (CS) is associated with skeletal muscle structural and functional impairment which may persist long‐term despite surgical removal of the source of cortisol excess. Prevalence of sarcopenia and its impact on Health‐Related‐Quality of Life (HRQoL) in 'cured' CS is not known. There is a need to identify easy biomarkers to help the clinicians recognise patients at elevated risk of suffering sustained muscle function. Patients and Methods: We studied 36 women with CS in remission, and 36 controls matched for age, body mass index, menopausal status, and level of physical activity. We analysed the skeletal muscle mass using dual‐energy X‐ray absorptiometry, muscle fat fraction using two‐point Dixon magnetic resonance imaging and muscle performance and strength using the following tests: hand grip strength, gait speed, timed up and go and 30‐s chair stand. We assessed HRQoL with the following questionnaires: SarQoL, CushingQoL, SF‐36. We calculated the sarcopenia index (SI; serum creatinine/serum cystatin C × 100). Results: Prevalence of sarcopenia, according to the European Working Group on Sarcopenia in Older People (EWGSOP), was greater in CS as compared with controls (19% vs. 3%; p  < .05). Patients with sarcopenia had a lower SarQoL score than those without sarcopenia (61 ± 17 vs. 75 ± 14; p  < .05), and scored worse on the items pain, easy bruising and worries on physical appearance ( p  < .05 for all comparisons) of the CushingQoL questionnaire. Patients with sarcopenia had poorer physical functioning on SF‐36 than those without sarcopenia (60 ± 23 vs. 85 ± 15; p  < .01). SI was lower in patients with sarcopenia than those without (71 ± 3 vs. 77 ± 2; p  = .032), and was associated with intramuscular fatty infiltration, worse performance on the 30‐s chair stand test, slower gait speed, and worse muscle weakness‐related HRQoL, as measured using the SarQoL questionnaire ( p  < .05). The optimised cut‐off value for the SI ratio to diagnose sarcopenia was 72, which yielded a sensitivity of 73% and a specificity of 90%. Conclusions: Sarcopenia is common in patients with CS in long‐term remission, and associated with impaired quality of life. The SI is a potential biomarker allowing clinicians to identify patients at high risk of muscle dysfunction.